2016
DOI: 10.1111/tmi.12762
|View full text |Cite
|
Sign up to set email alerts
|

Enteric fever in India: current scenario and future directions

Abstract: SummaryEnteric fever is a major cause of morbidity and mortality in tropical areas worldwide. The Indian subcontinent bears the brunt of the disease, both in terms of absolute case numbers and drugresistant strains. Recent phylogenetic studies suggest that the multidrug-resistant clade H58 originated in India and subsequently expanded through Asia and Africa. In Africa, it caused unrecognised outbreaks in areas previously considered free of the disease. In this study, we discuss the current status of enteric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 69 publications
2
32
0
Order By: Relevance
“…In this study, we found 58.4% and 0.84% of DCS and 37% and 89.9% of CiR strains among S. typhi and S. paratyphi respectively. Similar to our findings, several studies from India have reported high rate of resistance to Ciprofloxacin (23,26,28).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, we found 58.4% and 0.84% of DCS and 37% and 89.9% of CiR strains among S. typhi and S. paratyphi respectively. Similar to our findings, several studies from India have reported high rate of resistance to Ciprofloxacin (23,26,28).…”
Section: Discussionsupporting
confidence: 92%
“…DCS strains are associated with delayed clinical response and increase in complications. Accumulation of further mutations with or without added efflux pumps, lead to CiR (26). In this study, we found 58.4% and 0.84% of DCS and 37% and 89.9% of CiR strains among S. typhi and S. paratyphi respectively.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations